Evaluation of bivalve spat recruitment in artificial collectors to identify potential species for small-scale farming in the north Pacific coast of Colombia - Natasha Valencia-Martínez; Olivia Saiz-M; Diego Fernando Córdoba-Rojas; Alan Giraldo (Aquaculture Reports, 2023)
Decreases in fish stocks have led to new resource research, particularly in the Colombian Pacific where only a few species have traditionally been exploited. Among commercial species, bivalves are commonly implemented in small-scale aquaculture and their success and sustainability depend on consistent larval recruitment. Therefore, we evaluated the spat recruitment of some bivalves species and their potential for marine aquaculture in the north Colombian Pacific. To assess their potential, artificial substrates were exposed to different depths (3, 6, 9, and 12 m) during three immersion times (two, four, and six months) in five collecting stations along Bahía Cupica (Chocó department). Only Pinctada mazatlanica (Hanley, 1856) spat were recruited over the entire period, reaching up to 3.70 ± 5.76 individuals/collector (mean ± SD) on the external stations. Considering immersion times and depths, the highest recruitments were recorded after two months at 6 m depth. Also, two other species with potential commercial interest were recruited, Pinna rugosa Sowerby I, 1835 and Isognomon janus Carpenter, 1857. The densities and distributions of P. rugosa were very similar to P. mazatlanica; in turn, I. janus was the dominant species among the bivalve community. Hence, we highlight the potential of P. mazatlanica as an alternative resource in the north Colombian Pacific due to their continuous recruitment, as well as the potential exploitation of P. rugosa and I. janus due to their simultaneous recruitment. Furthermore, we highlight the benefits of cultivating these species, and particularly P. mazatlanica, as could significantly improve the economy and food security of local communities.